A Small-scale Investigation Of Critical Thinking Dispositions: The Case Of Second Year Foreign Languages Students At Rachid Ridha Al-achouri High School, Biskra - Hebiret, Sara; Bacher, Ahmed (جامعة الوادي - university of Eloued, 2022)
Critical thinking dispositions play a major role in the teaching and the learning processes of the thinking skills. In fact, critical thinking is viewed as "both a systemic inquiry and a mental attitude, a complex set of abilities and a process of dealing with ideas" (Cromwell, 1992, p. 39). EFL students ability to analyze or evaluate information, rules, or facts depends largely on their emotional readiness to be critical. If they choose not to exercise their thinking abilities, or they have not acquired the good thinking habits, those students may not be able to use the thinking skills. This would impede the development of critical thinking abilities in the EFL classrooms. The present paper is a small-scale investigation of critical thinking dispositions among second year high school students majoring in foreign languages at Rachid Rida AlAchouri in the willaya of Biskra. The questionnaire utilizes California Critical Thinking Dispositions Inventory (CCTDI) model advocated by Facione (1990). The CCTDI includes analycity, openmindedness, inquisitiveness, selfconfidence, truth-seeking, and systematicity thinking dispositions. The final findings show that all participants of the present study have more favorable dispositions towards analyticity, openmindedness, inquisitiveness, truth-seeking, self-confidence, and disinclination toward systematicity.
Article
Keywords: : critical thinking, dispositions, CCTDI, EFL, second year